Probing Physical Properties of a DNA-Protein Complex Using Nanofluidic Channels - Frykholm, Karolin; Alizadehheidari, Mohammadreza; Fritzsche, Joachim; Wigenius, Jens; Modesti, Mauro; Persson, Fredrik; Westerlund, Fredrik (Small (Weinheim an der Bergstrasse, Germany), 2014)
A method to investigate physical properties of a DNA‐protein complex in solution is demonstrated. By using tapered nanochannels and lipid passivation the persistence length of a RecA filament formed on double‐stranded DNA is determined to 1.15 μm, in agreement with the literature, without attaching protein or DNA to any handles or surfaces.